POFROIDISTINĖ MOKSLO FILOSOFIJOS TERAPIJA. - Juozelis, Evaldas (Problems / Problemos, 2012)
A uthorities of the philosophy of science Karl Popper and Adolf Grünbaum jointly repudiated the potential status of psychoanalysis as scientific edifice, though for particular methodological reasons. In the tradition of analytical philosophy psychoanalysis is widely considered pseudoscientific, despite the significant decrease of rationalist and positivist influence on philosophical discourse. However, during the last few decades moderate approaches of scientific knowledge evolved and appropriate socio-cultural and intellectual medium emerged, proposing particular therapies of post-Freudian psychoanalysis for the philosophy of science itself, since it allegedly suffers from certain ideological and methodological neuroses. Some authors, while offering certain remedies for academic discourse, insist on scientific status of psychoanalysis, others are certain that scientific status for psychoanalysis is neither necessary nor acceptable.